2008
DOI: 10.1080/14634980802319986
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater fishes and water status in México: A country-wide appraisal.

Abstract: México is the southernmost country in North America, and extends into Central America, south of the Isthmus of Tehuantepec. The northern half of México is located on the Temperate belt and is arid in character (Nearctic), while the rest is within the Tropical belt (Neotropical). Climate varies from extremely temperate desert in the north, to tropical humid in the south. México has more than 500 freshwater fish species, about 271 of them country endemics, and approximately 48 endemics from binational basins. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 15 publications
1
16
0
5
Order By: Relevance
“…Los avances en el conocimiento de las especies invasoras en México, permiten reconocer a los grupos exóticos como una de las principales causas de la extirpación de las nativas en más de 100 localidades en el país (Contreras-Balderas et al 2008, AguirreMuñoz & Mendoza-Alfaro 2009, esto las convierte en un componente importante dentro de las amenazas de extinción. El plan de manejo de la Reserva de la Biósfera, no contempla ninguna acción en respuesta a este proceso, a pesar de reconocer la presencia de especies no nativas en el área, (CONANP 2005) algunas clasificadas dentro de las 100 especies invasoras más dañinas a nivel global (Lowe et al 2004).…”
Section: Discusionunclassified
See 1 more Smart Citation
“…Los avances en el conocimiento de las especies invasoras en México, permiten reconocer a los grupos exóticos como una de las principales causas de la extirpación de las nativas en más de 100 localidades en el país (Contreras-Balderas et al 2008, AguirreMuñoz & Mendoza-Alfaro 2009, esto las convierte en un componente importante dentro de las amenazas de extinción. El plan de manejo de la Reserva de la Biósfera, no contempla ninguna acción en respuesta a este proceso, a pesar de reconocer la presencia de especies no nativas en el área, (CONANP 2005) algunas clasificadas dentro de las 100 especies invasoras más dañinas a nivel global (Lowe et al 2004).…”
Section: Discusionunclassified
“…La regulación de la actividad acuicultural en México no se cumple o no existe en el caso de las especies de uso ornamental (Contreras-Balderas et al 2008), la incorrecta regulación para la importación e introducción de nuevas especies al mercado, permite que prácticamente cualquier organismo acuático pueda ser introducido para ser cultivado con muy poco control, ha sucedido con la tortuga de concha blanda Apalone spinifera spinifera, ya que ejemplares de la misma han sido obtenidos y observados en el área de la REBIOSH (Castro-Franco & Bustos-Zagal 2004), por lo que forman parte de la fauna exótica, distinta a los peces comercializados en la región.…”
Section: Discusionunclassified
“…Fuller et al, 1999;Contreras-Balderas et al, 2008). Redbelly tilapia is a potential competitor with native fish for food and spawning areas in many places of United States and northwestern Mexico and is implicated in the decline of populations of the desert pupfish Cyprinodon macularius (Fuller et al, 1999;Varela-Romero et al, 2003).…”
mentioning
confidence: 97%
“…DISCUSSION-One of the main threats that face the native, freshwater fishes of North America is the introduction of exotic species of fishes (Fuller et al, 1999;Contreras-Balderas et al, 2008). Environments prone to establishment of exotic species include places having either low environmental resistance or low biological resistance (Case, 1991;Moyle and Light, 1996) as well as a low native-species richness (Elton, 1958;Orians, 1986;Lodge, 1993) such as occurs in the springs and oases of North American deserts (Douglas et al, 1994), including those of the Baja California peninsula , 2006b).…”
mentioning
confidence: 99%
“…It is unknown whether the species is established or not, but there is suspicion that it has hybridized with other species of the genus (Escalante and Contreras 1985). Cyprinella lutrensis (Baird & Girard, 1853) was documented by Contreras-Balderas et al (2008) as introduced, and mentioned it in multiple localities in the north. Ruiz-Campos et al (2012) suggested the species to be probably responsible of the decline of the Desert Pupfish Cyprinodon macularius Baird & Girard, 1853.…”
Section: Introductionmentioning
confidence: 99%